2019
DOI: 10.1515/cclm-2018-1236
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation reference intervals for pediatric hematology

Abstract: Background Interpreting hematology analytes in children is challenging due to the extensive changes in hematopoiesis that accompany physiological development and lead to pronounced sex- and age-specific dynamics. Continuous percentile charts from birth to adulthood allow accurate consideration of these dynamics. However, the ethical and practical challenges unique to pediatric reference intervals have restricted the creation of such percentile charts, and limitations in current approaches to laboratory test re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
58
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 31 publications
6
58
2
Order By: Relevance
“…In elderly patients, recruitment of ‘healthy’ individuals poses additional challenges due to the high prevalence of chronic diseases and prescription medication: exclusion of individuals according to these criteria leads to the selection of the ‘most healthy minority’, with questionable appropriateness of resulting reference intervals for the general population, and substantial practical obstacles when recruiting reference individuals. We circumvented these problems by using a data mining approach and applying an algorithm (Arzideh et al , ), that has been successfully used to evaluate paediatric (Zierk et al , , , ) and adult (Zierk et al , ) reference intervals in haematology, with the aim to define age‐ and sex‐specific reference intervals in the elderly. We did not collect any medical histories, but, starting with two very large datasets of routine clinical samples, we removed pathological samples in a five‐step process: (i) we excluded units and specialists caring for patients with a high expected fraction of haematologic abnormalities, (ii) we removed samples from patients with reduced renal function or acute‐phase reaction, (iii) we excluded samples with clearly abnormal test results in the same sample in other haematology analytes, (iv) we selected only one sample per patient, thereby reducing over‐representation of samples from chronically and critically ill patients, and (v) we calculated the distribution of physiologic measurements using an established algorithm (RLE), separating them from pathologic test results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In elderly patients, recruitment of ‘healthy’ individuals poses additional challenges due to the high prevalence of chronic diseases and prescription medication: exclusion of individuals according to these criteria leads to the selection of the ‘most healthy minority’, with questionable appropriateness of resulting reference intervals for the general population, and substantial practical obstacles when recruiting reference individuals. We circumvented these problems by using a data mining approach and applying an algorithm (Arzideh et al , ), that has been successfully used to evaluate paediatric (Zierk et al , , , ) and adult (Zierk et al , ) reference intervals in haematology, with the aim to define age‐ and sex‐specific reference intervals in the elderly. We did not collect any medical histories, but, starting with two very large datasets of routine clinical samples, we removed pathological samples in a five‐step process: (i) we excluded units and specialists caring for patients with a high expected fraction of haematologic abnormalities, (ii) we removed samples from patients with reduced renal function or acute‐phase reaction, (iii) we excluded samples with clearly abnormal test results in the same sample in other haematology analytes, (iv) we selected only one sample per patient, thereby reducing over‐representation of samples from chronically and critically ill patients, and (v) we calculated the distribution of physiologic measurements using an established algorithm (RLE), separating them from pathologic test results.…”
Section: Discussionmentioning
confidence: 99%
“…However, great care must be taken to avoid an unwarranted shift or widening of reference intervals in populations with a high prevalence of slightly abnormal test results. In previous work, we have shown that establishment of haematology reference intervals using a sophisticated data mining approach (the reference limit estimator, RLE) is feasible, even in the challenging setting of a tertiary care centre and a high proportion of abnormal test results (Zierk et al , , ). In short, this approach assumes a mixture of parametrically distributed samples from healthy individuals and pathologic samples.…”
mentioning
confidence: 99%
“…We employ an approach based on previous works by Arzideh et al 9,[16][17][18][19] and our experiences in their application to pediatric and adult datasets 8,[10][11][12][13] : This procedure is based on the assumption that the proportion of physiological samples in the input dataset can be modeled with a parametric distribution (so-called Power Normal distribution, a Gaussian distribution after Box-Cox transformation of the data, i.e. a distribution that can accommodate skewed data), and that a truncation interval T exists within the dataset, in which the proportion of abnormal test results is negligible.…”
Section: Methodsmentioning
confidence: 99%
“…As large numbers of test results are readily available from laboratory information systems, this enables the establishment of reference intervals specific to different populations, age-groups, analytical devices, and even batches and reagents. Extensive experience with these methods exists in children, where unique ethical challenges limit access to blood samples to create reference intervals 8,[10][11][12] and in challenging adult populations with a high proportion of patients with substantial morbidity and mortality 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation